Anti‐CD52 antibody treatment in murine experimental autoimmune encephalomyelitis induces dynamic and differential modulation of innate immune cells in peripheral immune and central nervous systems. Issue 3 (10th December 2021) - Barbour, Mark; Wood, Rachel; Harte, Tanith; Bushell, Trevor J.; Jiang, Hui‐Rong
Abstract: Anti‐CD52 antibody (anti‐CD52‐Ab) leads to a rapid depletion of T and B cells, followed by reconstitution of immune cells with tolerogenic characteristics. However, very little is known about its effect on innate immune cells. In this study, experimental autoimmune encephalomyelitis mice were administered murine anti‐CD52‐Ab to investigate its effect on dendritic cells and monocytes/macrophages in the periphery lymphoid organs and the central nervous system (CNS). Our data show that blood and splenic innate immune cells exhibited significantly increased expression of MHC‐II and costimulatory molecules, which was associated with increased capacity of activating antigen‐specific T cells, at first day but not three weeks after five daily treatment with anti‐CD52‐Ab in comparison with controls. In contrast to the periphery, microglia and infiltrating macrophages in the CNS exhibited reduced expression levels of MHC‐II and costimulatory molecules after antibody treatment at both time‐points investigated when compared to controls. Furthermore, the transit response of peripheral innate immune cells to anti‐CD52‐Ab treatment was also observed in the lymphocyte‐deficient SCID mice, suggesting the changes are not a direct consequence of the mass depletion of lymphocytes in the periphery. Our study demonstrates a dynamic and tissue‐specific modulation of the innate immune cells in their phenotype and function following the antibody treatment. The findings of differential modulation of the microglia and infiltrating macrophages in the CNS in comparison with the innate immune cells in the peripheral organs support the CNS‐specific beneficial effect of alemtuzumab treatment on inhibiting neuroinflammation in multiple sclerosis patients. Abstract : Anti‐CD52‐AB treatment in EAE mice: Increases expression of MHC‐II and costimulatory molecules on innate immune cells and their capacity of activating antigen specific T cells in the peripheral immune system, at one day but not three weeks after treatment. Reduces expression of MHC‐II and costimulatory molecules of innate immune cells in the CNS at both one day and three weeks after treatment. The transit response of peripheral innate immune cells to anti‐CD52‐Ab treatment is not a direct consequence of the mass depletion of lymphocytes in the periphery.